ZAWŁASZCZENIE NIERUCHOMOŚCI NA PRZYKŁADZIE DZIAŁAŃ WOJENNYCH Z POCZĄTKU XVII WIEKU W RZECZYPOSPOLITEJ OBOJGA NARODÓW. Z BADAŃ NAD PRAWEM ZDOBYCZY WOJENNEJ W EPOCE NOWOŻYTNEJ - Łopatecki, Karol (Zeszyty Prawnicze, 2017)
Property Requisition: A Case Study of early 17th-Century Military Operations for Research on the Early Modern Law on War Trophies Summary This article is on the requisitioning of property by soldiers stationing on enemy territory. The author presents the law on war trophies in force in Poland-Lithuania in 1609–1619, when the country was at war against the Grand Duchy of Muscovy. In particular he examines a protestation lodged by Stanisław Galiński, a Mazovian nobleman. This document provides evidence that pursuant to the Polish-Lithuanian law of war abandoned property could be lawfully requisitioned providing the party taking possession of the vacant real estate became its effective holder by taking over its management. This theory is confirmed by a 1613 parliamentary resolution which allowed for the confiscation of requisitioned property from soldiers who could not prove their title to tenure on these grounds. The legal situation of requisitioned properties was similar to that of property held by the Muscovite boyars of the Smolensk region, who were granted a conditional endorsement of tenure, with the recognition of a title in fee simple subject to enfeoffment by the king.